Integrasi Augmented Reality (AR) dalam LKPD pada materi gelombang cahaya untuk meningkatkan kemampuan spasial siswa SMA kelas XI - Dwi Fanni, Aria; Nasir, Muhammad; Zulhelmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine the validity and effectiveness of developing student worksheets (LKPD) integrated with Augmented Reality (AR) in improving spatial abilities on light wave material for grade XI high school students. This study used a Research and Development (R&D) approach with the ADDIE model combined with a quasi-experimental non-equivalent control group design. Data were collected through validation sheets, practicality questionnaires, and pretest-posttest of spatial abilities. The results showed that the AR-based LKPD was valid with an Aiken's V average of 0.910 and practical with a positive response from teachers and students. Inferential analysis using the Mann-Whitney U test showed a significance value of 0.001 < 0.05, and the N-Gain of the experimental class (0.5827) was higher than the control class (0.4128). It is concluded that the integration of AR in LKPD is effective in improving students' spatial abilities.